2015
DOI: 10.1007/s11356-015-4119-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic toxicity of emerging contaminants, alone or in combination, in Chlorella vulgaris and Daphnia magna

Abstract: This work presents the toxicity results of different compounds classified as emerging contaminants on primary producers and primary consumers in the aquatic compartment. The objectives were to (1) obtain acute and chronic toxicity results for algae and Daphnia magna using standardised or currently used tests, (2) study the relationship between the effects on the impaired feeding rate for daphnia and the effects of reproduction and (3) examine the responses on daphnia and algae after binary combinations of envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In addition, PFOS, when present in a pollutant mixture, can alter the toxicity of other pollutants and exacerbate the overall toxic response [30]. Furthermore, the impairments caused by PFOS can last for several generations [29], suggesting that chronic exposure will severely alter Daphnia population dynamics and possibly higher trophic levels [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PFOS, when present in a pollutant mixture, can alter the toxicity of other pollutants and exacerbate the overall toxic response [30]. Furthermore, the impairments caused by PFOS can last for several generations [29], suggesting that chronic exposure will severely alter Daphnia population dynamics and possibly higher trophic levels [19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, based on the mode of action, we predicted that the toxic response would increase with the number of contaminants present within the mixture. In addition, we predicted that mixtures containing PFOS might display enhanced or suppressed metabolic changes caused by interactions between PFOS and other contaminants, as previously demonstrated (Liu et al 2009;Pablos et al 2015). After contaminant exposure, metabolites from D. magna were analyzed using proton nuclear magnetic resonance ( 1 H NMR) to examine the relationship between metabolic profiles and contaminant mixture toxicity stress.…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies have found that toxicity decreased with the presence of PFOS in binary contaminant mixtures (Liu et al 2009;Rodea-Palomares et al 2012;Pablos et al 2015). Most of these contaminant mixtures that found a decrease in toxicity with POFS mixtures had a low log octanol-water partition coefficient (log K OW ), such as fluoxetine (Pablos et al 2015), propylparaben (Rodea-Palomares et al 2012), and atrazine (Liu et al 2009). Liu et al (2009) found that PFOS decreased the uptake of hydrophilic contaminants in cyanobacteria, thus revealing a potential mechanism of decreased toxicity with PFOS present in contaminant mixtures.…”
Section: Contaminant Mixtures With Propranololmentioning
confidence: 99%
“…The responses on Daphnia magna and Chlorella vulgaris after binary combinations of environmentally relevant compounds and perfluorooctane sulfonate (PFOS) was studied in the aquatic compartment (Pablos, et al, 2015). Ecotoxicological information about the toxicity of PCPs on aquatic organisms was also generated in the study.…”
Section: Environmental Toxicitymentioning
confidence: 99%